Time to retire 'New daily persistent headache': Mode of onset of chronic migraine and tension-type headache. (April 2022) - Lobo, Rhannon; Wang, Mu; Lobo, Sean; Bahra, Anish
Abstract: New daily persistent headache is described as an enigmatic condition with daily headache from onset. It has posed challenges diagnostically and therapeutically. Methods: We conducted a study of patients referred to headache services based in Central and North-East London, United Kingdom, meeting the International Classificaiton of Headache Disorders – 3 criteria for New daily persistent headache. Information on demographics, phenotype and treatment responses were collected. The syndrome of the daily headache was also classified according any other ICHD-3-defined syndrome. Results: Of 162 patients, females comprised 68.5% with median age of onset 35 years. The daily headache experienced was chronic migraine in 89.7% and tension-type headache in 8.8%. Thunderclap-onset New daily persistent headache occurred in 14.8%. More than one headache syndrome was experienced in 15.4%, including cough, hypnic, sexual and stabbing headache. All aura types were experienced, most commonly brainstem aura in 39%. Prior headache was reported 53.7%. A persisting sub-form was present in 51.2%, relapsing remitting in 12.3% and 14.0% reported improvement; 19.8% were lost to follow-up. Only 11.1% reported an antecedent trigger. The most common premorbid disorders were psychiatric in 35.7%. A fifth improved on preventative medication, most commonly amitriptyline, propranolol and topiramate. Conclusion: Our cohort of New daily persistent headache is consistent with a mode of onset of migraine and tension-type headache which occurs in predisposed individuals.